2010
DOI: 10.1152/ajpcell.00011.2009
|View full text |Cite
|
Sign up to set email alerts
|

Tumor necrosis factor-α causes release of cytosolic interleukin-18 from human neutrophils

Abstract: A. Tumor necrosis factor-␣ causes release of cytosolic interleukin-18 from human neutrophils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 68 publications
3
9
0
Order By: Relevance
“…In accordance with previous studies, mature IL-18 was only transiently detectable in neutrophil supernatants (22), despite that TLR stimulation upregulated intracellular pro-IL-18 in neutrophils. This may be the result of neutrophil reuptake of released IL-18 or degradation by released proteases.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In accordance with previous studies, mature IL-18 was only transiently detectable in neutrophil supernatants (22), despite that TLR stimulation upregulated intracellular pro-IL-18 in neutrophils. This may be the result of neutrophil reuptake of released IL-18 or degradation by released proteases.…”
Section: Discussionsupporting
confidence: 92%
“…These contradictory results regarding IL-18 incited us to perform additional experiments. Short-time stimulation with Clo97 triggered IL-18 secretion by PMNs; but in agreement with previous studies (22), the concentration of IL-18 rapidly returned to baseline levels (Fig. 6D).…”
Section: Neutrophil Conditioning Of Nk Cells Is Caspase Dependent Andsupporting
confidence: 92%
“…32 It has been reported that TNF- induced insulin resistance is associated with an elevated expression of IL-18 in human skeletal muscle tissue, which suggest, a possible role for IL-18 in the pathogenesis of TNF- induced insulin resistance in humans. 33,34 Also, it has been reported that antiinflammatory cytokines (IL-4, IL-10, IL-13, etc) counteracts the cytotoxic effects of proinflammatory cytokines, i.e. IL-1, TNF-, IL-17, etc in insulin-producing cells through the reduction of nitrosative stress.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, to gain insight into the neutrophil molecules involved in the activation of γδ T cells, we searched for factors secreted by activated neutrophils, which could play a role in the activation of T cells. Among these molecules, IL‐18 is an inflammatory cytokine produced by neutrophils in response to stimulation by TNF‐ α that promotes both the proliferation of CD8 + T cells stimulated by anti‐CD3 antibodies, and the expansion of natural killer cells in the presence of IL‐2 . Moreover, it was reported that IL‐18 stimulates the proliferation of γδ T cells activated by IL‐2 and zoledronate, and the blockade of the IL‐18R α chain strongly inhibits the proliferation of γδ T cells, suggesting the involvement of IL‐18 signalling .…”
Section: Resultsmentioning
confidence: 99%